Indeks Kepuasan Masyarakat Terhadap Pelayanan di Perpustakaan Daerah Kabupaten Hulu Sungai Utara - Siti Raudah; Risna Amalia (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
Abstract: This research is motivated by obstacles in fulfilling facilities, the absence of a waiting room in circulation services, the lack of staff, the presence of noise in the reading room area, and the lack of book updates. The purpose of this study is to determine the level of Public Satisfaction with Services at the Hulu Sungai Utara Regency Regional Library. The research method is descriptive quantitative, with a sample of 94 respondents. Data collection techniques are distributing questionnaires, observation, literature studies, and documentation. The sampling technique uses Probability Sampling, analyzing data using the perception value provision test. The results show that the index value obtained is 3.044 and the value of the public satisfaction index after being converted is 76.1, so the service quality is